PENGARUH GENDER, PENGHARGAAN FINANSIAL, PERTIMBANGAN PASAR KERJA, MOTIVASI KARIR, PENGAKUAN PROFESIONAL, LINGKUNGAN KERJA DAN PERSONALITAS TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK BERKARIER MENJADI AKUNTAN PUBLIK (Studi Kasus Pada Mahasiswa Akuntansi Universitas Muara Bungo) - Ronald N Gersang (Dhana, 2024)
This research aims to determine the influence of gender, financial rewards, job market considerations, career motivation, professional recognition, work environment and personality on accounting students' interest in becoming public accountants partially or simultaneously. The type of research used in this research is quantitative descriptive. The data used in this research are primary data and secondary data. The population in this study were students from the 2014-2016 Accounting Department at Muara Bungo University. The sample in this study was selected according to the criteria (purposive sampling) so that a sample of 96 people was obtained. The results of the research show that the partial test of the gender variable (X1) obtained a value of tcount (3.753) > ttable (1.985) and a value of sig (0.000) < (0.005), so that H0 was rejected and the 1 Ha hypothesis was accepted, the value of the financial reward variable (X2) was obtained. tcount (3.067) > ttable (1.985) and sig value (0.000) < (0.005), so that H0 is rejected and the 2 Ha hypothesis is accepted. The labor market consideration variable (X3) obtained a tcount value (-1.741) < ttable (1.985) and a sig value (0.085) > (0.005), so that H0 was accepted and the 3 Ha hypothesis was rejected. The career motivation variable (X4) obtained a tcount value (1.936) < ttable (1.985) and a sig value (0.056) > (0.005), so that H0 was accepted and the 4 Ha hypothesis was rejected. The professional recognition variable (X5) obtained a tcount value (1.840) < ttable (1.985) and a sig value (0.069) > (0.005), so that H0 was accepted and the 5 Ha hypothesis was rejected. The work environment variable (X6) tcount value (-5.865) > ttable (1.985) and sig value (0.000) < (0.005), so that H0 is rejected and the 2 Ha hypothesis is accepted. The personality variable (X7) obtained a value of tcount (9.705) > ttable (1.985) and a sig value (0.000) < (0.005), so that H0 was rejected and the 7 Ha hypothesis was accepted. This means that, partially, the variables Gender, Financial Rewards, Work Environment and Personality have a significant effect on Accounting Students' interest in pursuing a career as a public accountant (Y). Based on the results of the simultaneous test, the Fcount value is 17,340, which is greater than the Ftable of 2,200. So H0 is rejected and Ha is accepted. So it can be concluded that the variables Gender, Financial Rewards, Job Market Considerations, Career Motivation, Professional Recognition, Work Environment and Personality simultaneously have a positive and significant effect on the level of interest of Accounting Students in pursuing a career as a Public Accountant. Based on the coefficient of determination test, the R Square value is obtained at of 0.580 or 58%.